Music in Eighteenth-Century Austria - Wyn Jones, David (Cambridge Cambridge University Press, 1996)
Description Contents Resources Courses About the Authors The music of Haydn, Mozart and Beethoven forms a cornerstone of the modern repertoire, but very little is known about the context in which these composers worked. This volume of twelve essays by leading international scholars considers some of the musical traditions and practices of this little-understood period of music history. Beginning with the early decades of the eighteenth century, the volume documents selected aspects of musical life and style from the late Baroque period through to the early years of the nineteenth century. The four main areas covered in this exploration of music history are orchestral music, sacred music, opera and keyboard music. Georg Reutter (Haydn's teacher), Antonio Salieri (Mozart's colleague) and Wölffl (a rival of Beethoven) are just three of the period's prominent musicians who are discussed at length.
Preface -- Introduction: new challenges, new perspectives / David Wyn Jones -- The trumpet overture and sinfonia in Vienna (1715–1822): rise, decline and reformulation / A. Peter Brown -- The early Classical violin concerto in Austria / Chappell White -- Haydn's Missa sunt bona mixta malis and the a cappella tradition / David Wyn Jones -- Johann Baptist Vanhal and the pastoral mass tradition / Bruce MacIntyre -- The Austrian pastorella and the stylus rusticanus: comic and pastoral elements in Austrian music, 1750–1800 / Geoffrey Chew -- The applausus musicus, or Singgedicht: a neglected genre of eighteenth-century musical theatre / Robert N. Freeman -- The operas of Antonio Salieri as a reflection of Viennese opera 1770–1800 / John A. Rice -- Lorenzo da Ponte's Viennese librettos / Konrad Küster -- Viennese amateur or London professional? A reconsideration of Haydn's tragic cantata Arianna a Naxos / Julian Rushton -- The Viennese fortepiano in the eighteenth century / Eva Badura-Skoda -- The Beethoven-Wölfl piano duel / Tia DeNora
Keywords: Haydn, Joseph -- 1732-1809; Vanhal, Johann Baptist -- 1739-1813; Da Ponte, Lorenzo -- 1749-1838; Salieri, Antonio -- 1750-1825; Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); Music history; Symphony; Overture; Mass; Church music; Concerto; Cantata; A cappella; Opera; Music theater; Trumpet; Violin; Piano; Libretto; Pastoral; Amateur; Duel; Austria; Vienna (Austria)